Social media warfare and Kenya's conflict with Al Shabaab in Somalia: A right to know?. Issue 471 (5th September 2018) - Molony, Thomas
Abstract: This article explores Kenyan citizens' right to know details about sensitive security-related information in the context of a new era of social media warfare. It considers the public communications response to Al Shabaab's January 2016 attack on Kenya Defence Forces (KDF) personnel in El Adde, Somalia, and then to a similar attack in Kulbiyow a year later. Drawing on Twitter posts, an official account of Kenya's military activities in Somalia, and – unusually for the study of social media – on 'offline' methods of qualitative data collection, it asks why the KDF did not provide real-time updates about the El Adde attack, but did provide information about the assault on Kulbiyow? Three plausible explanations for the KDF's differing response are considered. First, at the time of El Adde, the KDF was inexperienced in terms of social media communication. Second, El Adde taught the KDF that in order not to lose the all-important public opinion, it had to match its enemy and also disseminate credible information. Finally, the strengthening voice of Kenyan citizens and the potential for further reputational damage pushed the KDF from a 'need-to-know' frame of mind in terms of its sharing of information, to more of a 'right-to-know' mentality.